Patchoulene Epoxide Isolated from Patchouli Oil Suppresses Acute Inflammation through Inhibition of NF-κB and Downregulation of COX-2/iNOS. (25th July 2017) - Liang, Jia-Li; Wu, Jia-Zhen; Liu, Yu-Hong; Zhang, Zhen-Biao; Wu, Qi-Duan; Chen, Han-Bin; Huang, Yan-Feng; Dou, Yao-Xing; Zhou, Jiang-Tao; Su, Zi-Ren; Zhan, Janis Ya-Xian
Abstract : According to the GC-MS analysis, compositional variation was observed between samples of patchouli oil, of which an unknown compound identified as patchoulene epoxide (PAO) was found only in the long-stored oil, whose biological activity still remains unknown. Therefore, the present study aimed to evaluate the potential anti-inflammatory activity with three in vivo inflammatory models: xylene-induced ear edema, acetic acid-induced vascular permeability, and carrageenan-induced paw edema. Further investigation into its underlying mechanism on carrageenan-induced paw edema was conducted. Results demonstrated that PAO significantly inhibited the ear edema induced by xylene, lowered vascular permeability induced by acetic acid and decreased the paw edema induced by carrageenan. Moreover, PAO markedly decreased levels of tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), interleukin-6 (IL-6), prostaglandin E2 (PGE2 ), and nitric oxide (NO), but increased levels of interleukin-4 (IL-4) and interleukin-10 (IL-10). PAO was also shown to significantly downregulate the protein and mRNA expressions of cyclooxygenase-2 (COX-2) and inducible nitric-oxide synthase (iNOS). Western blot analysis revealed that PAO remarkably inhibited p50 and p65 translocation from the cytosol to the nucleus by suppressing IKK β and I κ B α phosphorylation. In conclusion, PAO exhibited potent anti-inflammatory activity probably by suppressing the activation of iNOS, COX-2 and NF- κ B signaling pathways.